PENGOPTIMALISASI PENDIDIKAN KARAKTER DALAM PEMBELAJARAN KIMIA YANG EFEKTIF DAN EFISIEN DENGAN MEDIA INTERAKTIF - Jafrinta Irma Ruta Astari (J-PEK (Jurnal Pembelajaran Kimia), 2018)
Character education is a system of inculcating the values of the character to the school community which includes the components of knowledge, awareness and action to implement those values, both toward God Almighty, self, fellow, environment, and nationality. The role of teachers is very important in character education students. The application of character education in learning chemistry can significantly cultivate the commendable character and behavior of all learners so that the school will can to produce learners who are noble, qualified, skilled and competitive in all fields. The use of interactive online learning media gives effect to higher learning result of chemistry when compared with use of interactive offline.